Pengembangan Komposit Dari Karet Ebonit Dengan Penguat Serat Serabut Kelapa Untuk Komponen Otomotif Penutup Spion Sepeda Motor - Sadewa, Allan Budhi (2016)
Nowadays, rubber is used more widely from the simple one such as household appliances to automotive component. Using natural rubber as matrix with coconut husk fiber as reinforce will result in beneficial composite product in automotive component to be applied to motorcycle review mirror cover. This research aimed to find out the strength of coconut husk fiber with NaOH treatment and to find out the compulsive strength, izod impact, and hardness on varying fraction of fiber weight in the composite. The material used for developing composite was ebonite as matrix with of coconut husk fiber reinforce and with varying fiber weight fraction. The submerging process was carried out using NaOH 5% with varying submerging duration. Then, the rubber mixing process was carried out starting with mixing the natural rubber into chemicals and fiber using two-roll mill tool. Next, vulcanization was undertaken using slab-shaped mold at 150oC for 1.30 minutes. The composite was tested using standard ASTM D 638 for compulsive test, ASTM D 256 for izod impact test and SNI 0778 : 2009 for hardness test. The result of research showed that the highest mean compulsive strength of fiber was 138.642 N/mm2 occurring in submerging with NaOH 5% for 2 hours. The result of composite's compulsive test showed that the maximum compulsive strength of ebonite with fiber weight fraction of 40 phr as 4.717 Mpa and maximum tension in ebonite with fiber weight fraction of 20 phr was 37.33% and the highest mean modulus of elasticity in ebonite with fiber weight fraction of 40 phr was 17.76 Mpa. The result of izod impact test found that the highest mean was 1.448 J/mm2 in ebonite with fiber weight fraction of 0 phr. For the data of hardness testing result, it could be found that the highest mean was obtained in ebonite with fiber weight fraction of 0 phr was 91 A shore scale. Keywords: ebonite, coconut fiber, NaOH, two-roll mill, vulcanization